Field validation of fibre Bragg grating sensors for measuring strain on driven steel piles. Issue 2 (1st February 2015) - McAVOY, C.; Byrne, B. W.; Schroeder, F. C.; Taborda, D. M. G.; Preston, J.; Sideri, M.; Zdravković, L.; Burd, H. J.; Igoe, D.; Kallehave, D.; Doherty, P.; Muir Wood, A.; et al.
Abstract : In recent years, fibre Bragg grating (FBG) sensors have emerged as a relatively new strain sensing technology for civil engineering applications. This paper presents a field trial to assess the feasibility of using FBG sensor arrays to measure strain in driven steel piles. Two FBG arrays were installed in grooves within the wall of an open-ended steel pile such that the finished profile was completely flush with the pile shaft. The pile was then driven into a dense sand deposit using an impact hammer to provide the required installation energy. The FBG gauges were monitored throughout driving in conjunction with accelerometers to quantify the scale of the hammer impacts. The FBG sensors were subjected to hammer blows that yielded pile accelerations between 500  g and 1400  g during installation. The fibre optic sensors were measured throughout driving, where they were observed to respond to the hammer impacts, showing a rapid increase in strain and a return to their initial values between hammer strikes. After installation, a lateral load test was performed with independent load measuring devices. Excellent agreement was observed between the measured moments and those inferred from the FBG strain output. The output of this trial demonstrates that FBG strain sensors are a viable means of measuring load transfer in foundation systems and are suitably robust to withstand high pile driving accelerations.